2017
DOI: 10.1016/j.jbo.2017.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

An integrative analysis of DNA methylation in osteosarcoma

Abstract: BackgroundThe study aimed to analyze aberrantly methylated genes, relevant pathways and transcription factors (TFs) in osteosarcoma (OS) development.MethodsBased on the DNA methylation microarray data GSE36002 that were downloaded from GEO database, the differentially methylated genes in promoter regions were identified between OS and normal samples. Pathway and function enrichment analyses of differentially methylated genes was performed. Subsequently, protein-protein interaction (PPI) network was constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…[ 41 , 42 ] Moreover, cellular growth and differentiation are key processes for carcinoma development and progression. The findings in our study are consistent with recently reported results, [ 43 ] which show that neuroactive ligand-receptor interaction and the PPAR signaling pathway are highly associated with osteosarcoma.…”
Section: Discussionsupporting
confidence: 94%
“…[ 41 , 42 ] Moreover, cellular growth and differentiation are key processes for carcinoma development and progression. The findings in our study are consistent with recently reported results, [ 43 ] which show that neuroactive ligand-receptor interaction and the PPAR signaling pathway are highly associated with osteosarcoma.…”
Section: Discussionsupporting
confidence: 94%
“…Their potential targeting genes were then clearly shown to us. Among these potential targeting genes, many have been reported to participate in the process of OS, such as cell adhesion molecule 1 (CADM1) [ 18 ], early B cell factor 2 (EBF2) [ 19 ], MAX interactor 1 (MXI1) [ 20 ], and nemo-like kinase (NLK) [ 21 ]. It indicated that these differentially expressed miRNAs may play critical regulating roles in the progression of OS.…”
Section: Discussionmentioning
confidence: 99%
“…In the PPI network, the MAXI interactor signals transducer 1 (MXI1), the transcription activator STAT3 and the T-cell acute lymphocytic leukemia 1 (TAL1) had the highest degree of hypermethylation. These genes were identified as being associated with cancer and were hypermethylated in OS cells (80).…”
Section: Role Of Epigenetic Mechanismsmentioning
confidence: 99%